Creso - Draghi, Antonio,Minato, Niccolò,Eleonore,Leopold,Cosmerovius, Johann Christoph (Cosmerovio, 1678)
Deutsche Drucke zur Festkultur des Barock (1601-1700)
Bibliogr. Nachweis: Thiel, Libretti Nr. 500
Keywords: Quelle; CD-ROM; Libretto; Festbeschreibung